Computational physics : problem solving with computers - Landau, Rubin H.; Páez Mejía, Manuel José; Bordeianu, Cristian C. (Weinheim : Wiley-VCH, 2007)
Computing software basics -- Errors and uncertainties in computations -- Object-oriented programming: kinematics -- Integration -- Differentiation -- Trial and errror searching -- Matrix computing and N-D Newton Raphson -- Data fitting -- Deterministic randomness -- Monte Carlo applications -- Thermodynamic simulations: ising model -- Computer hardware basics: memory and CPU -- High-performance computing: profiling and tuning -- Differential equation applications -- Quantum eigenvalues via ODE matching -- Fourier analysis of linear and nonlinear signals -- Unusual dynamic of nonlinear systems -- Differential chaos in phase space -- Fractals -- Parallel computing -- Parallel computing with MPI -- Electrostatics potentials via finite differences (PDEs) -- Heat flow -- PDE waves on strings and membranes -- Solitons; KdeV and Sine-Gordon -- Quantum wave packets -- Quantum paths for functional integration -- Quantum bound states via integral equations -- Quantum scattering via integral equations.
Incluye referencias bibliográficas e índice
Keywords: Física -- Problemas, ejercicios, etc -- Procesamiento electrónico de datos; Física matemática; Física -- Simulación por computadores